TINGKULUAK DI NAGARI KOTO NAN GADANG KOTA PAYAKUMBUH PROVINSI SUMATERA BARAT - Hurahmi, Intah Mifta; Efi, Agusti; Novrita, Sri Zulfia (Journal of Home Economics and Tourism, 2015)
The purpose of this research is to describe about the form, the technique and making the philosophical meaning of tingkuluak at Nagari Koto Nan Gadang Payakumbuh, West Sumatera Province. The type of this research is qualitative. The data source are primary and secondary data. The collecting technique of the data using observation, interviews and documentation. The result of this research are : 1) The form of Nagari Koto Nan Gadang Payakumbuh West Sumatera Province’s has many variation, there are : a) The form of tingkuluak which like buffalo horn with the blunt, tip called tingkuluak baikek, b) The big tingkuluak, where at the top of the head of tingkuluak is like chimney, the name of this tingkuluak is tingkuluak kompong and tingkuluak talakuang putiah but this tingkuluak is bigger than tingkuluak kompong. c) The tingkuluak which has a simple form, on the side of this tingkuluak is upright and it’s called tingkuluak bugih. 2) The technique of making tingkuluak is first tingkuluak baikek, by wrapped the tingkuluak two times, to the head so it is like buffalo horn but the end is blunt and the technique to make tingkuluak kompong and tingkuluak talakuang putiah are by slung the tingkuluak on the head, but it is made big like chimney but tingkuluak talakuang putiah is bigger than tingkuluak kompong and to make tingkuluak bugih is by slung the tingkuluak on the head and at the end of the fabric is up. 3) The philosophical meaning of the tingkuluak baikek are brave, fair, persevring and never give up. The tingkuluak kompong has the meaning a modesty. Tingkuluak bugih has the meaning a friendly and persevering and the tingkuluak talakuang putiah has meaning simplicity and the holy of our religion.Keywords: Tingkuluak, tingkuluak baikek, tingkuluak kompong, tingkuluak talakuang putiah dan tingkuluak bugih